Quillbot Web-Application: Utilizing Online Technology on Academic Writing at an Indonesian Islamic Higher Education - Jaladara, Andi Rifqah; Jafar, Muhammad Basri; Salija, Kisman (Har Press Indonesia, 2023)
The objectives of this research were to find out the impact and obstacles that QuillBot's utilization as an online technology faced on students’ academic writing. This research used a phenomenological qualitative design. The subjects were eight students who participated in this research. This research used an interview guide to collect the data. The result showed that the impact of QuillBot as an online technology on students’ academic writing has a positive and negative impact, where the positive is that QuillBot can help students save their time to write the academic writing process, increase their vocabulary, and help in the writing process with the complexity, objectivity, formality, and hedging aspects of academic writing itself. The negative impact indicates the students’ dependence on QuillBot tools, where they become lazy to think and do not use their ability to write their academic writing. Finally, there were the obstacles that students encountered while using QuillBot, such as a bad network and a lack of clear instructions on how to upgrade to the premium version.